The Athletic Shoe in Football: Apparel or Protective Equipment?. (March 2017) - Jastifer, James; Kent, Richard; Crandall, Jeff; Sherwood, Chris; Lessley, David; McCullough, Kirk A.; Coughlin, Michael J.; Anderson, Robert B.
Background: Foot and ankle injuries are common in sports, particularly in cleated athletes. Traditionally, the athletic shoe has not been regarded as a piece of protective equipment but rather as a part of the uniform, with a primary focus on performance and subjective feedback measures of comfort. Changes in turf and shoe design have poorly understood implications on the health and safety of players. Evidence Acquisition: A literature search of the MEDLINE and PubMed databases was conducted. Keywords included athletic shoewear, cleated shoe, football shoes, and shoewear, and search parameters were between the years 2000 and 2016. Study Design: Clinical review. Level of Evidence: Level 5. Results: The athletic shoe is an important piece of protective sports equipment. There are several important structural considerations of shoe design, including biomechanical compliance, cleat and turf interaction, and shoe sizing/fit, that affect the way an athlete engages with the playing surface and carry important potential implications regarding player safety if not understood and addressed. Conclusion: Athletic footwear should be considered an integral piece of protective equipment rather than simply an extension of the uniform apparel. More research is needed to define optimal shoe sizing, the effect that design has on mechanical load, and how cleat properties, including pattern and structure, interact with the variety of playing surfaces.